The ameliorative effect of curcumin extract on the morphological and skeletal abnormalities induced by sunset yellow and tartrazine in the developing chick embryo Gallus domesticus - El-Borm, Hend T. (Heliyon, 2020)
Previous studies have suggested that food dyes are responsible for causing number of health problems. The study under consideration aims to show the possible morphological and skeletal malformation induced due to in ovo administration of sunset yellow (SY) and tartrazine (Tz) with or without curcumin (Cur) during organogenesis of developing chick embryo at doses 1.575mg/egg, 0.375mg/egg and 3mg/kg eggs for SY, Tz and Cur comparing with control. The investigation revealed evident reduction in the weight and length of embryos as well as malformations in feather, head, and limbs. Most of the congenital malformations were seen in SY and Tz injected groups such as short beak, excencephaly, kniked tail and pygostyle, curved scapula and retardation in the degree of ossification were the most evident in endoskeleton malformation. In addition, the length of ossified long bones in SY and Tz groups was affected. Co-administration of Cur with SY and Tz ameliorate the reversed effect of SY and Tz on the shape, length, body weight and skeleton of embryos.